Pengaruh literasi keuangan, pendapatan orang tua, dan gaya hidup hedonis terhadap perilaku keuangan mahasiswa - Pratama, Ikhtyar; Jasman, Jumawan; Saharuddin, Saharuddin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to gain knowledge about the effect of financial literacy on financial behavior, how influential parents' income (parental income) on financial behavior and how much influence hedonic lifestyle has on financial behavior. The method chosen in this experiment is multiple regression analysis with the test media taken is SPSS22. The total population in this study was 1031 people with a sample obtained from the slovin formula count of 91 people. The results of this study state that financial literacy affects financial behavior, parental income affects financial behavior, hedonic lifestyle affects financial behavior. So it can be said that the thought about financial literacy obtained will have an impact on individual financial decisions on the use of their funds, as well as lifestyle and financial behavior having the skills to manage time and finances to use their funds as effectively as possible.